RELATIONSHIP MAINTENANCE OF SWALLOW BIRDS WITH EDUCATION,TRAINING,MOTIVATION,SKILL AND POLICY TO INCRESE BUSINESS PERFORMANCE: ( Study in Tempe Lake, South Sulawesi Province Indonesia) - AMIRUDDIN; NOR AZRIN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
The objectives of this research consist of several objectives, including: 1. Calculating the magnitude of the effect of the variables of education, training, skills, motivation, policies on the performance of the swiftlet business, 2.Analyze and calculate the direct and indirect effects of education, training, skills, motivation and policies on the performance of the swallow business. 3.Analyze and calculate the single effect, simultaneous influence and mutual interaction between the variables of education, training, skills, motivation, policies in influencing the performance of the swallow bird business, 4.Examine the role of the skill variable in mediating the education and training variables in influencing the motivation and performance of the swallow bird business 5. Testing the role of policy variables in moderating motivational variables in influencing swallow business performance, 6. Build and simulate a dynamic model of a swallow nest maintenance system integrated with agriculture and SMEs (down stream) using the results of an empirical study of the effect of all variables on increasing business performance, and 7. Run model simulations at various technology and management level scenarios to predict and evaluate their impact on sustainability and profitability in an integrated swallow bird maintenance system with agriculture and SMEs (down stream). The method of research was used the mixed method quantitative and qualitative research. The number of samples used in this study amounted to 184 respondents who will be taken using random sampling. The data analysis data was used SEM (Statistical Equation Model). The result of the research are Education has a significant effect on skills, training has a significant effect on skills, education has no significant effect on motivation, training has a significant effect on motivation, skills have no significant effect on motivation, education has no significant effect on business performance, training has no significant effect on business performance, skills have no effect significant effect on business performance, motivation has a significant effect on business performance, policy has no significant effect on business performance, there is an indirect effect of education on motivation through skills, there is no indirect effect of training on motivation through skills, and the policy variable is not a moderator variable between motivation with business performance. Implication of this research is rearing swallows with education, training, motivation, skills and policies can improve the business performance of swallow nest entrepreneurs so that they can get prosperity and develop their business.